Plumbagin, a natural derivative of 1,4-naphthoquinone, induces cyclopic phenomenon via increased apoptosis and ROS generation in the early stage of zebrafish embryos - Yeonju Lim; Chaeeun Kim; Donghyeon Kim; Myoung-Jin Kim; Ji-Woo Yu; Min-Ho Song; Yurim Kim; Junhee Son; Ji-Ho Lee; Sung-Eun Lee (Ecotoxicology and Environmental Safety)
Plumbagin (PL; 5-hydroxy-2-methyl-1,4-naphthoquinone) is an analogue of juglone (JG) with additional methylation on carbon 2. It has been found in fungi, insects, and plants, especially Malaysian persimmons, and plants containing PL are globally used as folk medicines. Among 1,4-naphthoquinones tested in this study, PL and JG exhibited high lethality towards zebrafish (Danio rerio) embryos and reduced their hatchability, and induced morphological changes. In addition, zebrafish embryos exposed to 0.13 µM of PL at 4 h post-fertilization exhibited severely reduced brain differentiation in a PL concentration-dependent manner, resulting in severe cyclopia symptoms, with individuals experiencing cyclopia ultimately dying. The cyclopia induced by PL was more severe than that of the positive controls, ethanol, forskolin, and cyclopamine. Increased apoptosis and reactive oxygen species (ROS) generation were associated with PL-induced cyclopia, and concurrent treatments with ROS-quenching curcuminoids decreased cyclopia. Metabolomic activity in PL-treated embryos was also severely disrupted, and even surviving individuals would likely not retain proper function. Thus, plants should be monitored for the presence of PL, given its strong cyclopia-inducing effects on animals. Due to the high frequency and severity of symptomatic zebrafish embryos in this study, PL’s association with holoprosencephaly, specifically cyclopia, is undeniable.